PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA PT KISEL (ANAK PERUSAHAAN PT TELKOMSEL) MEDAN - Siregar, Muhammad Yamin; Ningsih, Intan Wahyu (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2016)
The objective of this research is to determine the impact of service quality dimension viewed from tangible,Â  reliability,Â  responsiveness,Â  assurance,Â  andÂ  empathyÂ  dimensionÂ  towardsÂ  customer satisfaction at PT. Kisel (Official Branch of PT. Telkomsel) Medan.In this research the populationâs 103Â  respondentÂ  withÂ  sampleâsÂ  usedÂ  isÂ  82Â  respondent.Â  TheÂ  sampleÂ  selectionÂ  methodÂ  usedÂ  is purposive sampling, based on Telkomsel customer that visit PT Kisel to complaint their problem moreÂ  thanÂ  1Â  time.Â  DataÂ  analyzingÂ  methodÂ  thatÂ  isÂ  usedÂ  isÂ  multipleÂ  linearÂ  regressionÂ  usingÂ  SPSS version 19.0 program.The result of this research isÂ  tangible, reliability, responsiveness, assurance, empathy simultaneously have positive and significant influencetoward customer satisfaction. Based onÂ  testÂ  onlyÂ  reliabilityÂ  variableÂ  andÂ  assuranceÂ  haveÂ  significantÂ  influenceÂ  towardsÂ  customer satisfaction. based on coefficient determination test (Â  R2) 86,3% of customer satisfaction can be explained by tangible, reliability, responsiveness, assurance, and empathy, while the rest 13,7% is explained by other variables not observed in this research.Keywords :Tangible, Reliability, Responsiveness, Empathy, Customer satisfaction